Activity of cefiderocol against high-risk clones of multidrug-resistant Enterobacterales, Acinetobacter baumannii, Pseudomonas aeruginosa and Stenotrophomonas maltophilia - Delgado-Valverde, Mercedes; Conejo, M del Carmen; Serrano, Lara; Fernández-Cuenca, Felipe; Pascual, Álvaro (Journal of antimicrobial chemotherapy, 2020)
Abstract Background Cefiderocol is a novel siderophore cephalosporin, developed for activity against MDR Gram-negative bacilli (MDR-GNB). Objectives To assess the in vitro antibacterial activity of cefiderocol against a collection of MDR-GNB clinical isolates from hospitals in southern Spain. Methods Two hundred and thirty-one isolates of successful clones were tested: 125 Enterobacterales (121 ESBL- and/or carbapenemase-producing Klebsiella pneumoniae and 4 carbapenemase-producing Enterobacter cloacae), 80 Acinetobacter baumannii, 6 Pseudomonas aeruginosa and 20 Stenotrophomonas maltophilia. Ceftolozane/tazobactam, ceftazidime, ceftazidime/avibactam, cefepime, aztreonam, meropenem, amikacin, ciprofloxacin, colistin and tigecycline were used as comparators against Enterobacterales, P. aeruginosa and A. baumannii. Minocycline, levofloxacin and trimethoprim/sulfamethoxazole were studied against S. maltophilia instead of aztreonam, ciprofloxacin and cefepime. MICs were determined by broth microdilution according to CLSI guidelines. MIC determination was performed in CAMHB for all antimicrobials except cefiderocol, where iron-depleted CAMHB was used. Results Cefiderocol showed potent in vitro activity against the isolates analysed. MIC50 and MIC90 values were in the ranges 0.125–8 mg/L and 0.5–8 mg/L, respectively, and 98% of isolates were inhibited at ≤4 mg/L. Only five isolates showed cefiderocol MICs of >4 mg/L: three ST2/OXA-24/40-producing A. baumannii, one ST114/VIM-1-producing E. cloacae and one ST114/VIM-1 + OXA-48-producing E. cloacae. All KPC-3-producing K. pneumoniae were susceptible to cefiderocol, even those resistant to ceftazidime/avibactam. P. aeruginosa isolates showed cefiderocol MICs of <4 mg/L, including those resistant to ceftolozane/tazobactam. S. maltophilia isolates displayed cefiderocol MICs of <4 mg/L, including those resistant to levofloxacin and/or trimethoprim/sulfamethoxazole. Conclusions Cefiderocol showed excellent activity against MDR-GNB, including carbapenem-resistant isolates, and was the most active antimicrobial tested against this collection.